Role of Maternal Vitamin D3 Levels in Shaping Adolescent Vascular Health: Evidence From a Spanish Population‐Based Birth Cohort - Júlia Sangüesa; Sandra Márquez; Parisa Montazeri; Silvia Fochs; Nuria Pey; Augusto Anguita‐Ruiz; Charline Warembourg; Elke Rouxel; Tim Nawrot; Patrick De Boever; Bart Elen; Diana B. P. Clemente; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Low gestational vitamin D levels may increase offspring risk of cardiovascular disease from an early age. Studies investigating the impact on offspring macrovascular function have been inconsistent. Few included pulse wave velocity as an arterial stiffness indicator, and none included measures of microvascularization as an early marker of cardiovascular health. This study explored the association between gestational vitamin D levels and macro‐ and microvascular health across early adolescence. Methods and Results We analyzed data from 430 mother–child pairs from a Spanish birth cohort. 25‐hydroxyvitamin D3 (vitamin D3) levels were measured in serum at 13 weeks of pregnancy. At 11 and 15 years we assessed macrovascular parameters, including systolic and diastolic blood pressure (mm Hg) and pulse wave velocity (m/s), and microvascular parameters (central retinal artery/vein equivalent (μm)). We used continuous (in ng/mL) and categorical (deficient <20 ng/mL versus adequate >20 ng/mL) deseasonalized 25(OH)D3 levels as exposure. Mixed effect and linear regression models were conducted. During their pregnancies, nearly 23% of the mothers had deficient vitamin D3 levels. We did not find statistically significant associations between pregnancy vitamin D3 levels and macro‐ and microvascular function markers across adolescence. However, subjects exposed to deficient vitamin D3 levels showed a nonstatistically significant decrease in pulse wave velocity (β=−0.09 [95% CI, −0.19 to 0.01]) compared with those exposed to adequate levels. There was no evidence of a sex interaction. Conclusions Our findings show little evidence to support associations between low vitamin D levels during pregnancy and macro‐ or microvascular health parameters through early adolescence.